Promethazine-induced neuroleptic malignant syndrome under general anesthesia: a case report - Liu, Peng; Liao, Zhi-Min (Frontiers in Psychiatry, 2026)
BackgroundNeuroleptic malignant syndrome (NMS) is a rare yet life-threatening disease that is often induced by antipsychotic medications.Case presentationIn this study, we describe a case of a 13-year-old female who developed NMS following promethazine use during general anesthesia. This is expected to provide clinicians, particularly anesthesiologists, with crucial insights that will improve the perioperative identification and management of this condition. The patient manifested classic clinical features of NMS, including hyperpyrexia, autonomic dysfunction, and generalized rigidity. However, the patient’s serum creatine phosphokinase (CPK) levels were within normal limits, demonstrating the heterogeneous presentation of the disorder. The main interventions included drugs targeting to achieve airway control, physical cooling, hemodynamic stabilization, and symptomatic management, which promoted the patient’s gradual recovery.ConclusionThis case illustrates that due to individual variations, even standard drug dosages may induce neuroleptic malignant syndrome (NMS). Notably, NMS lacks specific laboratory findings, and its diagnosis must rely on clinical symptoms to avoid delays in early identification and treatment.